PELATIHAN PENYUSUNAN SOAL HIGHER ORDER THINKING SKILLS (HOTS) DI SMK PEMBANGUNAN DENPASAR - Ni Putu Meina Ayuningsih; Ni Made Dwijayani; Ketut Gus Oka Ciptahadi (STMIK Royal, 2020)
Abstract: The low HOTS (Higher Order Thinking Skills) students based on the results of PISA 2015 in mathematics shows the characteristics of mathematics learning are still familiar with Lower Order Thinking Skills (LOTS) questions. Based on this, HOTS math problems need to be developed at the Vocational high school education level. The difficulty of the teacher in applying HOTS questions is due to the lack of information obtained by the teacher and the lack of sharing activities to compile HOTS questions. The purpose of this community service activity is to provide training for vocational mathematics teachers in making HOTS questions. This community service activity is in the form of training for Mathematics Teachers of Denpasar Development Vocational School and involving all teachers of mathematics subjects. The partner in this dedication activity named I Made Surya Mega Widiastha, S.Pd is one of the mathematics teachers at the Denpasar Development Vocational School. The implementation of community service activities is carried out through three stages, namely planning, implementation, and reflection. Based on the results of the questionnaire given to the partners and to the school, the results of the service have been able to run well. Keywords: Dedication, Mathematics, Training, Hots Abstrak: Rendahnya HOTS (Higher Order Thinking Skills) siswa berdasarkan hasil PISA 2015 dalam matematika menunjukkan karakteristik pembelajaran matematika masih terbiasa dengan soal-soal Lower Order Thinking Skills (LOTS). Berdasarkan hal tersebut, perlu dikembangkan soal matematika HOTS di jenjang pendidikan sekolah menengah Kejuruan. Kesulitan guru dalam menerapkan soal-soal HOTS dikarenakan kurangnya informasi yang diperoleh guru serta minimnya kegiatan sharing untuk menyusun soal HOTS. Tujuan kegiatan pengabdian masyarakat ini untuk memberikan pelatihan bagi guru matematika SMK dalam membuat soal-soal HOTS. Kegiatan pengabdian masyarakat ini berupa pelatihan kepada guru matematika SMK Pembangunan Denpasar dan melibatkan semua guru mata pelajaran matematika. Mitra pada kegiatan pengabdian ini bernama I Made Surya Mega Widiastha, S.Pd merupakan salah satu guru matematika di SMK Pembangunan Denpasar. Pelaksanaan kegiatan pengabdian masyarakat ini dilakukan melalui tiga tahapan, yaitu perencanaan, implementasi, dan refleksi. Berdasarkan hasil kuisioner yang diberikan kepada pihak mitra maupun ke pihak sekolah diperoleh hasil pengabdian sudah dapat berjalan dengan baik. Kata kunci: Pengabdian, Matematika, Pelatihan, Hots